A new nurse frog of Allobates masniger-nidicola complex (Anura, Aromobatidae) from the east bank of Tapajós River, eastern Amazonia - de Lima Moraes, Leandro João Carneiro; Pavan, Dante; Lima, Albertina Pimentel (Zootaxa, 2019)
The small nurse frogs of the genus Allobates (Anura, Aromobatidae) represent one of the most challenging taxonomic issues of the Neotropics. During several amphibian surveys in the Middle Tapajós River region, state of Pará, Brazil, we collected phenotypic, ecological, and molecular data on species of this genus, leading to the identification of a new species included in the Allobates masniger-nidicola complex. The new species is characterized by a large body size (snout-vent length 19.2–21.7 mm in males and 19.3–22.0 mm in females), finger III not swollen in adult males; cryptic external coloration, with dorsum uniformly ochre; a dark brown lateral stripe and a pale cream ventrolateral stripe; limbs ranging from ochre to orange; throat and chest violaceous in males and yellowish in females. The advertisement call is usually arranged in bouts of four closely spaced notes, which we term 4-pulsed units of repetition (UR), 0.317 s long on average, followed by silent intervals, and an average dominant frequency of 4.163 kHz. The new species also has exotrophic tadpoles with a unique fin morphology, which begins after the body-tail insertion and is deeper posteriorly to half of the caudal length. Sequencing of the 16S and COI regions of the mitochondrial DNA show a genetic p-distance of approximately 6–10% compared to closely related congeners. We discuss the biogeography of the new species based on phylogenetic relationships of the species within the Allobates masniger-nidicola complex and the allopatric geographic distribution in relation to sister taxa. Functional characteristics and geographic restrictions make this species particularly sensitive to the increasing human impact in eastern Amazonia.